Visual and proprioceptive contributions to postural control of upright stance in unilateral vestibulopathy. (2nd April 2016) - Eysel-Gosepath, Katrin; McCrum, Christopher; Epro, Gaspar; Brüggemann, Gert-Peter; Karamanidis, Kiros
Abstract: Preserving upright stance requires central integration of the sensory systems and appropriate motor output from the neuromuscular system to keep the centre of pressure (COP) within the base of support. Unilateral peripheral vestibular disorder (UPVD) causes diminished stance stability. The aim of this study was to determine the limits of stability and to examine the contribution of multiple sensory systems to upright standing in UPVD patients and healthy subjects. We hypothesized that closure of the eyes and Achilles tendon vibration during upright stance will augment the postural sway in UPVD patients more than in healthy subjects. Seventeen UPVD patients and 17 healthy subjects performed six tasks on a force plate: forwards and backwards leaning, to determine limits of stability, and upright standing with and without Achilles tendon vibration, each with eyes open and closed (with blackout glasses). The COP displacement of the patients was significantly greater in the vibration tasks than the controls and came closer to the posterior base of support boundary than the controls in all tasks. Achilles tendon vibration led to a distinctly more backward sway in both subject groups. Five of the patients could not complete the eyes closed with vibration task. Due to the greater reduction in stance stability when the proprioceptive, compared with the visual, sensory system was disturbed, we suggest that proprioception may be more important for maintaining upright stance than vision. UPVD patients, in particular, showed more difficulty in controlling postural stability in the posterior direction with visual and proprioceptive sensory disturbance.